2022
DOI: 10.3390/biomedicines10040866
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3B System Dysregulation Contributes to the Hypomethylated State in Ischaemic Human Hearts

Abstract: A controversial understanding of the state of the DNA methylation machinery exists in ischaemic cardiomyopathy (ICM). Moreover, its relationship to other epigenetic alterations is incomplete. Therefore, we carried out an in-depth study of the DNA methylation process in human cardiac tissue. We showed a dysregulation of the DNA methylation machinery accordingly with the genome-wide hypomethylation that we observed: specifically, an overexpression of main genes involved in the elimination of methyl groups (TET1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Besides environmental and genetic causative factors, the epigenetic regulation of CVD-related genes is associated with the development and progression of multiple CVD [ 14 ]. In this Special Issue, Tarazón et al observed a genome-wide hypomethylation in cardiac tissue samples of ischemic cardiomyopathy patients, which was related to changes in the DNMT3B system, the main DNA methyltransferase [ 15 ]. Overall, this study provides additional evidence to strengthen the potential of targeting epigenetic key enzymes for CVD treatment.…”
mentioning
confidence: 99%
“…Besides environmental and genetic causative factors, the epigenetic regulation of CVD-related genes is associated with the development and progression of multiple CVD [ 14 ]. In this Special Issue, Tarazón et al observed a genome-wide hypomethylation in cardiac tissue samples of ischemic cardiomyopathy patients, which was related to changes in the DNMT3B system, the main DNA methyltransferase [ 15 ]. Overall, this study provides additional evidence to strengthen the potential of targeting epigenetic key enzymes for CVD treatment.…”
mentioning
confidence: 99%